2015
DOI: 10.1155/2015/793764
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Preferentially Induces Clinical Remission and Mucosal Healing in Short Course Crohn’s Disease with Luminal Lesions through Balancing Abnormal Immune Response in Gut Mucosa

Abstract: This study was undertaken to evaluate the efficacy of infliximab (IFX) in treatment of Crohn's disease (CD) patients. 106 CD patients were undergoing treatment with IFX from five hospitals in Shanghai, China. Clinical remission to IFX induction therapy was defined as Crohn's disease activity index (CDAI) < 150. Clinical response was assessed by a decrease in CDAI ≥ 70, and the failure as a CDAI was not significantly changed or increased. Ten weeks after therapy, 61 (57.5%) patients achieved clinical remission,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 40 publications
1
36
1
Order By: Relevance
“…In a long‐term follow‐up of an RCT, significantly higher MH rates of 72.0% compared to 28.6% were observed in early versus late/conventional treatment group . Similar trends were observed in five observational studies in a real‐world setting …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…In a long‐term follow‐up of an RCT, significantly higher MH rates of 72.0% compared to 28.6% were observed in early versus late/conventional treatment group . Similar trends were observed in five observational studies in a real‐world setting …”
Section: Resultssupporting
confidence: 77%
“…Nine publications showed that early treatment leads to better mucosal healing rates (29.0%‐72.0%) compared with late/conventional treatment (12.9%‐62.2%) . In an RCT the rate of mucosal healing was 45.9% vs 30.3% (n = 244, P = .010) in tight control vs conventional treatment group .…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated the mechanisms whereby SNIP1 expression was downregulated in the IEC from inflamed intestinal mucosa of IBD patients. As accumulating evidences have shown that elevated proinflammatory cytokines (e.g., TNF-a, IFN-g, IL-1b, IL-6, and IL-17A) are common features of intestinal mucosal inflammation and play a crucial role in the pathogenesis of IBD, 14,15 we detected the expression of TNF-a, IL-1b, IL-6, IFN-g, and IL-17A mRNA in inflamed mucosa of active IBD patients. Linear cor-relation analyses revealed that IEC-derived SNIP1 mRNA expression was inversely correlated with expression of TNF-a, IL-1b, and IL-6 mRNA, respectively, in the inflamed mucosa from active CD ( Supplementary Figure S2a-e) and UC patients (Supplementary Figure S2f-j).…”
Section: Tnf-a Downregulates Snip1 Expression In Iecmentioning
confidence: 86%
“…Clinical remission was defined as a CDAI score of <150 points, and clinical response as a decrease in the CDAI score ≥70 points at the evaluation time point in comparison with the baseline index. The failure category included all the remaining patients, whose CDAI was not significantly changed or increased 20 28 29. Endoscopic response to IFX therapy was also assessed at week 12 after initial administration and endoscopic variables were scored according to the Simple Endoscopic Severity for CD (SES-CD) as described elsewhere 30 31.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatants were harvested and analysed by sandwich ELISA kits for TNF-α, IFN-γ, IL-17A, IL-4 and IL-10 production using cytokine-specific kits according to our previous report 32. Moreover, cultured cells were also collected by extraction of total RNA, and mRNA levels for IL-17A, retinoic acid receptor-related orphan receptor C (RORC), IFN-γ, TNF-α, T-bet, IL-4, Gata3, IL-10 and Foxp3, respectively, were analysed using qRT-PCR as described previously 28 32 33…”
Section: Methodsmentioning
confidence: 99%